The concept and features of staffing of the State Criminal Executive Service and probation bodies in Ukraine - K. Yu. Sverdlin (Law and Safety)
The sphere of criminal penalties in our country has been undergoing reform for many years, and even today, in the context of Ukraine's opposition to the open full-scale military invasion of the russian federation, the work on transforming and improving the national penitentiary system has not stopped. The Ukrainian government, in cooperation with the international community, academics and civil society, has already taken a number of important steps to humanise the system. At the same time, some rather important problematic issues on this path have not yet received proper scientific and theoretical study or legislative regulation, in particular, the problem of staffing the State Criminal Executive Service of Ukraine and authorised probation bodies. The current Strategy for Reforming the Penitentiary System of Ukraine describes the problems of staffing in a rather superficial and fragmentary way, in fact, everything is reduced to its purpose and most important tasks. Obviously, this approach does not contribute to the improvement of the principles and mechanisms of this provision, nor to the efficiency and quality of the reform of the penitentiary system as a whole.